PENGARUH AUDIT INTERNAL TERHADAP EFEKTIVITAS PELAKSANAAN SISTEM PENGENDALIAN INTERN PADA PP. BPR TUTUR GANDA PAMANUKAN SUBANG - Hari Satia Nugraha (LPPM STIKes SITI HAJAR dan Insight Power, 2022)
The purpose of this study is to test empirically whether internal audit which consists of Independence, Professional Expertise, Scope of Work, Implementation of Audit Work, Management of the Internal audit section, influences the partial and simultaneous on the effectiveness of the implementation of the internal control structure. This research was conducted at PT. BPR DOUBLE SPEECH Pamanukan Subang in Subang, West Java Province. Data was collected by distributing questionnaires to the heads of the respective Internal Control Units, and the heads of the Ministry of Finance. The method used in this research is to use a quantitative descriptive analysis method. To test the hypothesis used multiple linear regression analysis model, the test used by SPSS 17.0. The results of the study show that independence affects the effectiveness of the internal control structure implementation. Professional expertise affects the effectiveness of the implementation of the internal control structure. The scope of work affects the effectiveness of the implementation of the internal control structure. Implementation of audit work affects the effectiveness of the implementation of the internal control structure. Management of the internal audit section affects the effectiveness of the implementation of the internal control structure. Independence, professional expertise, scope of work, implementation of audit work, and management of the internal audit department simultaneously affect the effectiveness of the implementation of the internal control structure. Keyword: Audit, Effectiveness, Simultaneous